Endovascular equipoise shift in a phase III randomized clinical trial of sonothrombolysis for acute ischemic stroke. (July 2019) - Alexandrov, Andrei V.; Tsivgoulis, Georgios; Köhrmann, Martin; Katsanos, Aristeidis H.; Soinne, Lauri; Barreto, Andrew D.; Rothlisberger, Travis; Sharma, Vijay K.; Mikulik, Robert; Muir, Keith W.; Levi, Christopher R.; Molina, Carlos A.; et al.
Background: Results of our recently published phase III randomized clinical trial of ultrasound-enhanced thrombolysis (sonothrombolysis) using an operator-independent, high frequency ultrasound device revealed heterogeneity of patient recruitment among centers. Methods: We performed a post hoc analysis after excluding subjects that were recruited at centers reporting a decline in the balance of randomization between sonothrombolysis and concurrent endovascular trials. Results: From a total of 676 participants randomized in the CLOTBUST-ER trial we identified 52 patients from 7 centers with perceived equipoise shift in favor of endovascular treatment. Post hoc sensitivity analysis in the intention-to-treat population adjusted for age, National Institutes of Health Scale score at baseline, time from stroke onset to tPA bolus and baseline serum glucose showed a significant (p < 0.01) interaction of perceived endovascular equipoise shift on the association between sonothrombolysis and 3 month functional outcome [adjusted common odds ratio (cOR) in centers with perceived endovascular equipoise shift: 0.22, 95% CI 0.06–0.75; p = 0.02; adjusted cOR for centers without endovascular equipoise shift: 1.20, 95% CI 0.89–1.62; p = 0.24)]. After excluding centers with perceived endovascular equipoise shift, patients randomized to sonothrombolysis had higher odds of 3 month functional independence (mRS scores 0–2) compared with patients treated with tPA only (adjusted OR: 1.53; 95% CI 1.01–2.31; p = 0.04). Conclusion: Our experience in CLOTBUST-ER indicates that increasing implementation of endovascular therapies across major academic stroke centers raises significant challenges for clinical trials aiming to test noninterventional or adjuvant reperfusion strategies.